Sinorhizobium fredii Strains HH103 and NGR234 Form Nitrogen Fixing Nodules With Diverse Wild Soybeans (Glycine soja) From Central China but Are Ineffective on Northern China Accessions - Francisco Temprano-Vera; Dulce Nombre Rodríguez-Navarro; Sebastian Acosta-Jurado; Xavier Perret; Romain K. Fossou; Pilar Navarro-Gómez; Tao Zhen; Deshui Yu; Qi An; Ana Maria Buendía-Clavería; Javier Moreno; Francisco Javier López-Baena; et al. (Frontiers in Microbiology, 2018)
Sinorhizobium fredii indigenous populations are prevalent in provinces of Central China whereas Bradyrhizobium species (Bradyrhizobium japonicum, B. diazoefficiens, B. elkanii, and others) are more abundant in northern and southern provinces. The symbiotic properties of different soybean rhizobia have been investigated with 40 different wild soybean (Glycine soja) accessions from China, Japan, Russia, and South Korea. Bradyrhizobial strains nodulated all the wild soybeans tested, albeit efficiency of nitrogen fixation varied considerably among accessions. The symbiotic capacity of S. fredii HH103 with wild soybeans from Central China was clearly better than with the accessions found elsewhere. S. fredii NGR234, the rhizobial strain showing the broadest host range ever described, also formed nitrogen-fixing nodules with different G. soja accessions from Central China. To our knowledge, this is the first report describing an effective symbiosis between S. fredii NGR234 and G. soja. Mobilization of the S. fredii HH103 symbiotic plasmid to a NGR234 pSym-cured derivative (strain NGR234C) yielded transconjugants that formed ineffective nodules with G. max cv. Williams 82 and G. soja accession CH4. By contrast, transfer of the symbiotic plasmid pNGR234a to a pSym-cured derivative of S. fredii USDA193 generated transconjugants that effectively nodulated G. soja accession CH4 but failed to nodulate with G. max cv. Williams 82. These results indicate that intra-specific transference of the S. fredii symbiotic plasmids generates new strains with unpredictable symbiotic properties, probably due to the occurrence of new combinations of symbiotic signals.